The physical universe - Krauskopf, Konrad Bates (McGraw-Hill Higher Education, 2006)
Aimed at presenting the essentials of physics, chemistry, earth science, and astronomy in a clear, easy-to-understand way, The Physical Universe shows students how science works, how scientists approach problems, and why science constantly evolves in its search for understanding.